Wide Cytokine Analysis in Cerebrospinal Fluid at Diagnosis Identified CCL-3 as a Possible Prognostic Factor for Multiple Sclerosis - Puthenparampil, Marco; Stropparo, Erica; Zywicki, Sofia; Bovis, Francesca; Cazzola, Chiara; Federle, Lisa; Grassivaro, Francesca; Rinaldi, Francesca; Perini, Paola; Sormani, Maria Pia; Gallo, Paolo (Frontiers in Immunology, 2020)
Background. Apart from IgG oligoclonal bands, no other biomarker has been up to date validated for diagnostic and/or prognostic purposes in Multiple Sclerosis (MS). Aim. To investigate a wide panel of cytokines and chemokines in the cerebrospinal fluid (CSF) of relapse-onset MS (RMS) patients and evaluate their association with clinical and magnetic resonance imaging (MRI) parameters, as well as their predictive clinical value. Methods. Fifty RMS and 11 healthy controls (HC) underwent brain MRI (including 3D-T1, 3D-FLAIR and 3-DIR sequences) and CSF examination. Eighty-seven cytokines and chemokines were analyzed in CSF by Multiplex technology. Results. Compared to HC, CXCL13, CCL22, MIP-1α, CCL1, IL-16, CXCL11, CXCL10, CXCL6, CXCL9, CCL19, and CCL23 were significantly (p<0.05) increased in RMS CSF. However, only MIP-1α was associated with MS diagnosis (OR=95.4, 95%CI: 1.9-4846.6, p=0.02). Based on a 95%CI in HC (cut-off value: 0.736 pg/mL) and ROC analysis (cut-off value: 0.495 pg/mL), RMS patients were stratified in MIP1αhigh (>0.736 pg/mL), MIP1αmedium and MIP1αlow (<0.495 pg/mL). Survival analysis disclosed a strong association between high MIP-1α values and disease reactivation (OR=4.9, 95%CI: 1.8-13.3, p<0.005) in the following two years. Conclusions. MIP1α deserves further investigation as candidate prognostic biomarker for RMS.